Cervical Spondylotic Amyotrophy: Case Series and Review of the Literature - Takahashi, Toshiyuki (Neurospine, 2019)
OBJECTIVE: Cervical spondylotic amyotrophy (CSA) is a relatively rare entity caused by cervical degenerative spinal diseases and characterized by motor weakness accompanied by remarkable muscle atrophy in the upper extremities without significant sensory deficits or spastic paraparesis in the lower extremities. Postoperative outcomes and predictive prognostic factors vary among previous reports. In the present report, we describe the surgical results in patients who were surgically treated for CSA and present a literature review. METHODS: In total, 33 patients with CSA were retrospectively analyzed. Correlations between the surgical outcome and the following factors were statistically analyzed: age, sex, type of impaired muscle, preoperative severity of motor weakness, number of levels of cord or root compression, presence of a T2 high-intensity area in the spinal cord, cervical kyphosis, and methods of surgical procedure. RESULTS: On postoperative neurological evaluation, 25 patients (75.8%) had favorable outcomes and 8 had unfavorable outcomes (proximal type, 72.2%; distal type, 78.6%). Patients with favorable outcomes were significantly younger than those with unfavorable outcomes (p=0.013). Patient’s characteristics except for age and radiological factors were not correlated to surgical outcome. CONCLUSION: The present study focused on the surgical results in patients who were surgically treated for CSA along with updated information from a literature review. Improvement of motor weakness is expected with acceptable prevalence although higher age can be a negative factor. Surgical outcomes and predictive factors related to a poor prognosis were determined and compared with those of previous articles.